Iktikad Tidak Baik dalam Pendaftaran dan Model Penegakan Hukum Merek di Indonesia - Mukti Fajar; Yati Nurhayati; Ifrani Ifrani (Fakultas Hukum Universitas Islam Indonesia, 2018)
Trade mark not only functions as an identity but also contains economic value so there are many efforts regarding bad-faith trademark registration. This study aimed to find the concept of bad-faith registration and to know the law enforcement in Indonesia. This was a normative legal research, with statute approach, conceptual approach, and case approach. The results of the study showed that: first, the concept of bad-faith has been regulated in Trademark Law Number 19 of 1992, Trademark Law Number 15 of 2001 and Law Number 20 of 2016. The concept of bad-faith is when an applicant is reasonably suspected to register his trade mark improperly and dishonestly to imitate, copy, or follow the trade mark of other parties for the interests of his business, create unfair business competition atmosphere, deceive, or mislead consumers. Second, the law enforcement on bad-faith trade mark registration is carried out by (a) rejecting the trade mark since registration process; (b) removal of trade mark by trade mark owners, government (ministers) or third parties; (c) revocation of trade mark by lawsuit in Commercial Court.